Exploring Knowledge and Perceptions of Generic Medicines Among Drug Retailers and Community Pharmacists - Basak, S. C. (Medknow Publications & Media Pvt Ltd, 2012)
The study was carried out to evaluate community pharmacists’ and drug retailers’ knowledge and perceptions about generic medicines. A cross-sectional descriptive study, with a questionnaire, was conducted to survey community pharmacists and drug retailers working in 39 randomly selected private pharmacies from two towns of Tamil Nadu, India. Among 66 respondents (pharmacists and drug retailers), 39 (59.1%) were drug retailers; 52 (78.8%) were self-employed; majority in the age group 31-40 (31.8%); and mostly males (83.3%). Overall, 21 respondents (31.8%) did not know what generic medicines were. About 30% of the respondents thought that generic medicines are of inferior quality compared to branded medicines. Only 63.6% of the surveyed pharmacists and drug retailers agreed that generic medicines can be considered therapeutically equivalent with the branded ones. A higher level of education had a direct relationship having correct knowledge of generic medicines (P<0.01). The majority of the respondents (80%) did not support generic substitution, even in case of prescribed medicines are not available. Many community pharmacists and drug retailers have misconceptions regarding generic medicines. Lack of knowledge may negatively affect the community pharmacists’ support towards generic medicines in India. This issue should be addressed by academicians and other relevant bodies.